Robotic and laparoscopic right anterior sectionectomy and central hepatectomy: multicentre propensity score-matched analysis. Issue 4 (9th February 2022) - Yang, Hye Yeon; Choi, Gi Hong; Chin, Ken-Min; Choi, Sung Hoon; Syn, Nicholas L.; Cheung, Tan-To; Chiow, Adrian K. H.; Sucandy, Iswanto; Marino, Marco V.; Prieto, Mikel; Chong, Charing C.; Lee, Jae Hoon; et al.
Abstract : Both robotic and laparoscopic right anterior sectionectomy and central hepatectomy can be performed safely in expert centres, with excellent outcomes. The robotic approach was associated with statistically significant less blood loss compared with laparoscopy, although the clinical relevance of this finding remains unclear.